Poligonų ir aplinkinių miškų medžių pažeidimų kulkomis ir skeveldromis tyrimas - Misevičius, Gintautas; Puškorius, Stasys; Vilutienė, Valentina (Lietuvos matematikos rinkinys, 2011)
Trees surrounding a training ground are damaged by bullets during shooting practice. A part of splinters of cartridges and explosives fly over the protective ramparts, thus causing a threat for safety and damaging trees of surrounding forests deteriorating the valuable resources. In the paper, an analysis of damage caused by bullets and splinters to trees of forests surrounding Kairiai training ground is carried out by applying mathematical methods. The mathematical formulas for calculation of the probabilities of the distance of deviation of a bullet from the center of the target, for identification of the safe height of the rampart and simulation of distribution of the zones where the speed of shot bullets can be dangerous for humans are provided.